2014
DOI: 10.1159/000363133
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Injection of CD34+-Cells in Chronic Ischemic Heart Failure: 7 Years Follow-Up of the DanCell Study

Abstract: Objectives: Seven years ago, the DanCell study was carried out to test the hypothesis of improvement in left ventricular ejection fraction (LVEF) following repeated intracoronary injections of autologous bone marrow-derived stem cells (BMSCs) in patients suffering from chronic ischemic heart failure. In this post hoc analysis, the long-term effect of therapy is assessed. Methods: 32 patients [mean age 61 (SD ± 9), 81% males] with systolic dysfunction (LVEF 33 ± 9%) received two repeated intracoronary infusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The only other study which investigated repeated cell administration in the setting of chronic heart failure, the DanCell study, recently reported 7-year follow-up clinical data of the 32 patients, who received intracoronary infusion of autologous BM-MNC. 18 At 7 years, mortality was 31%, and patients, who received a higher number of CD34+ cells, showed a better survival compared with patients who received low numbers of CD34+ cells, a finding which remained significant in a multivariate analysis. However, the trial comprised only 32 patients compared with our 297 patients, and no comparison was performed to a control group or heart failure score.…”
Section: Discussionmentioning
confidence: 88%
“…The only other study which investigated repeated cell administration in the setting of chronic heart failure, the DanCell study, recently reported 7-year follow-up clinical data of the 32 patients, who received intracoronary infusion of autologous BM-MNC. 18 At 7 years, mortality was 31%, and patients, who received a higher number of CD34+ cells, showed a better survival compared with patients who received low numbers of CD34+ cells, a finding which remained significant in a multivariate analysis. However, the trial comprised only 32 patients compared with our 297 patients, and no comparison was performed to a control group or heart failure score.…”
Section: Discussionmentioning
confidence: 88%
“…In three, patients were assigned to receive immuno-selected CD34 + cells or placebo [38,39,77], whereas in the others, patients received unselected BM-MNCs or placebo [98,99]. The cells were mostly delivered via direct catheter-based endomyocardial injections using either the NOGA™ System [39,40,55,76,77,80,[99][100][101], or the Biocardia Helix™ catheter [53,102], or via the IC route [38,103,104]. Trans-epicardial BM-MNC implantation was performed as an adjunct to CABG surgery in four studies [105][106][107][108].…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…The total mortality at the five-year FU was also lower for patients who received 113 ± 26 × 10 6 CD34 + cells IC than controls (14% vs 35%) [29]. Two IC infusions (four months apart) of high dose autologous BM-MNCs (1533 ± 765 × 10 6 BM-MNCs, including 23 ± 11 × 10 6 CD34 + cells and 14 ± 7 × 10 6 CD133 + cells) were performed in a non-randomized manner on 32 patients with chronic systolic dysfunction (LVEF 33 ± 9%) [104]. According to the median number of CD34 + cells they received, there was a trend towards decreased mortality (3 vs 7 patients), readmission rate (5 vs 7 patients), and morbidity at the seven-year FU for patients who received 32 ± 9 × 10 6 CD34 + cells versus those who received15.5 × 10 6 CD34 + cells.…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…However, a pooled analysis of 7 randomized controlled trials enrolling 660 patients with AMI stated that bone MSC infusion at 4 to 7 days after AMI held greater improvement in LVEF and reduction of LV end-systolic dimensions compared to cell infusion within 24 hours which might link to the occurrence of acute inflammatory reactions immediately after AMI [ 99 ]. Besides, five-year follow-up study of intracoronary BMMNC infusion in 8 patients with stable severe ICM indicated no significant change in systolic and diastolic function [ 100 ], but 7-year follow-up of the DanCell study proved a beneficial effect of bone marrow-derived stem cells engrafting in patients suffering from chronic ischemic heart failure [ 31 ]. The cardiac improvement was also associated with the seriousness of patient's condition.…”
Section: Influence Factors Of Stem Cell Therapy For Icmmentioning
confidence: 99%